Establishing a Network for Promoting Rational Drug Use in Khok Samrong District, Lopburi Province. - Poungpradab, Pongsak (Journal of Public Health and Innovation, 2026)
This study was a Participatory Action Research (PAR) aimed at establishing a Rational Drug Use (RDU) promotion network in Khok Samrong District, Lopburi Province. The research was conducted through the PAR cycle, consisting of four stages: Planning, Action, Monitoring and Evaluation, and Lessons Learned and Replanning.. The study population comprised 265 Village Health Volunteers (VHVs) under Sub-district Health Promoting Hospitals in Khok Samrong District, who were responsible for consumer protection activities in the community. The results revealed that most participants had a moderate level of knowledge regarding the use of antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) (67.9%). Attitudes toward rational drug use were also at a moderate level ( = 2.01, S.D. = 0.15). A comparison of mean scores before and after the capacity-building intervention showed statistically significant differences at the 0.01 level (p-value < 0.0001), with higher post-intervention knowledge and attitude scores. Furthermore, a five-month follow-up indicated improved community drug use behaviors, including a reduction in self-medication, antibiotic use, and non-steroidal anti-inflammatory drugs use. In conclusion, the findings suggest that strengthening the role of the RDU network in providing continuous health education through appropriate media and community-based activities is essential. This approach can effectively change misconceptions and reduce inappropriate drug use behaviors, leading to sustainable rational drug use in the long term.